Specificity of psychological readiness for changes and personality’s maturity of the employees of the state criminal and executive service - O. V. Mitroshkina (Law and Safety)
The work focuses on the study of psychological readiness for changes and personality’s maturity among the employees of the State Criminal and Executive Service of Ukraine. It is shown that readiness for changes in the reforming conditions is a psychological condition for successful professional activity and personal self-realization of the staff of the criminal and executive service. The content of the concepts of “psychological readiness” and “psychological readiness for changes” is revealed; the purposefulness of the study of personality’s maturity as one of the factors of psychological readiness for changes is substantiated. The purpose of the study was to identify the features of the functioning of psychological readiness for changes in the context of personal maturity of the employees of the State Criminal and Executive Service of Ukraine.